3D Printing of Photocrosslinked Alginate Dialdehyde-Gelatin Hydrogels Reinforced with Cobalt-Containing Mesoporous Bioactive Glass Nanoparticles for Developing Skin Wound Dressings - Zeimaran, Ehsan; Pourshahrestani, Sara; Röder, Jonas; Detsch, Rainer; Boccaccini, Aldo R. (Advanced Materials Interfaces, 2025)
Designing three-dimensional (3D)-printable hydrogels presents a significant challenge, particularly in maintaining the polymer concentration at minimal levels while ensuring that the printing process can be cell-friendly at room temperature. This study aims to examine the feasibility of designing multi-crosslinked hydrogels composed of methacrylate-functionalized alginate dialdehyde (ADAMA) and different concentrations of gelatin methacrylate (GelMA). Cobalt-doped mesoporous bioactive glass nanoparticles (Co-MBGNs) are incorporated into the hydrogels to further tailor their mechanical and biological properties. The hydrogels, crosslinked under UV and immersed in calcium chloride solution, show high elasticity and fatigue resistance over five compression cycles. The inclusion of Co-MBGNs enhances the mechanical properties while cell viability is higher in the pure polymeric hydrogels. The nanocomposites promote cell aggregate formation. The non-cytotoxic hydrogel supernatants induce NHDF cell migration at rates similar to or even faster than the control group. The printability of hydrogels is also examined through extrusion-bioprinting approach. The room-temperature printing is only possible for the hydrogels made of 5 wt% of GelMA and 2.5 wt% of ADAMA. The 3D-printed constructs show impressive elasticity and are easy to handle. These findings can offer valuable insights into the development of mechanically robust and customizable wound dressings.
CRIS-Team Scopus Importer:2025-04-11
Keywords: GelMA; mesoporous bioactive glass nanoparticles; methacrylated alginate dialdehyde; printable hydrogels; wound healing

Antibacterial polylysine-containing hydrogels for hemostatic and wound healing applications: preparation methods, current advances and future perspectives - Pourshahrestani, Sara; Zeimaran, Ehsan; Fauzi, Mh Busra (Biomaterials Science, 2024)
The treatment of various types of wounds such as dermal wounds, multidrug resistant bacteria-infected wounds, and chronic diabetic wounds is one of the critical challenges facing healthcare systems. Delayed wound healing can impose a remarkable burden on patients and health care professionals. In this case, given their unique three-dimensional porous structure, biocompatibility, high hydrophilicity, capability to provide a moist environment while absorbing wound exudate, permeability to both gas and oxygen, and tunable mechanical properties, hydrogels with antibacterial function are one of the most promising candidates for wound healing applications. Polylysine is a cationic polymer with the advantages of inherent antibacterial properties, biodegradability, and biocompatibility. Therefore, its utilization to engineer antibacterial hydrogels for accelerating wound healing is of great interest. In this review, we initially discuss polylysine properties, and then focus on the most recent advances in polylysine-containing hydrogels (since 2016) prepared using various chemical and physical crosslinking methods for hemostasis and wound healing applications. Finally, the challenges and future directions in the engineering of these antibacterial hydrogels for wound healing are discussed.
CRIS-Team Scopus Importer:2024-07-12

The effect of mesoporous bioactive glass nanoparticles incorporating various metallic ions (Cu, Zn, Mn, Te) on wound healing - Pourshahrestani, Sara; Zeimaran, Ehsan; Janko, Christina; Alexiou, Christoph; Kerpes, Andrea; Würz, Adrian; Fischer, Marcus; Kaňková, Hana; Hartmann, Martin; Boccaccini, Aldo R. (Materials Advances, 2024)
Recently, mesoporous bioactive glasses (MBGs) as microparticles or nanoparticles (MBGNs) aroused a great interest owing to their high textural properties and capability to be incorporated with biologically active ions desirable for different stages of wound healing. Considering therapeutic effects of two well-recognized elements (copper and zinc) as well as two less-common elements (manganese and tellurium), in this study, different concentrations of these elements were incorporated into SiO2-CaO MBGNs and their potential for wound healing applications was assessed in vitro. While at a concentration of 5 mg ml−1, the extracts of some MBGNs reduced E. coli and S. aureus bacteria viabilities, normal human dermal fibroblast (NHDF) cell viabilities were negatively affected with extracts of Cu-MBGNs and Te-MBGNs. The nanoparticles also affected hemolysis in a donor-dependent manner and the incorporation of Te into the MBGNs networks increased the hemolysis ratio to more than 5%. Moreover, some of the nanoparticles at concentration of 1 mg ml−1 shortened activated partial thromboplastin time (aPTT) insignificantly compared to pure platelet poor plasma. At higher concentrations of therapeutic elements, the extracts of nanoparticles resulted in the significant slower migration of NHDF cells in the scratch area. The effects of the nanoparticles and their extracts on blood coagulation and NHDF cell migration are thus dependent on the composition and/or applied concentration of nanoparticles. The present results provide information for the design of MBGN compositions of interest for wound healing and highlight the importance of optimization of the nanoparticles dosage and therapeutic ion concentration for acceleration of the wound healing process.
CRIS-Team Scopus Importer:2024-08-09